Trace metal speciation in coastal and off-shore sediments from Ross Sea (Antarctica) - IANNI, MARIA CARMELA; MAGI, EMANUELE; SOGGIA, FRANCESCO; RIVARO, PAOLA FRANCESCA; FRACHE, ROBERTO (Microchemical Journal, 2010)
The information on total metal concentration in sediments is not sufficient to assess the metal behaviour in the environment, while speciation studies are more effective in estimating environmental impact of contaminated sediments. Concerning metal distribution in Antarctic marine sediments, several studies reported total or extractable (by means of a unique reagent) content, but only few publications dealt with metal speciation. This work presents the total content and speciation pattern of Al, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn in 12 cm sediment cores, sampled both in coastal and off-shore sites of the Ross Sea shelf area, within the framework of the Italian National Antarctic Programme (PNRA). The total content results of metals are comparable with the background values and the speciation highlights good environmental quality of the studied areas. Only Cd and Pb, in fact, are present in significative amount in non residual phases (acid-extractable and reducible, respectively).